Eliminating the high abortion related complications and deaths in Cameroon: the restrictive legal atmosphere on abortions is no acceptable excuse - Luchuo Engelbert Bain; Eugene Justine Kongnyuy (BMC, 2018)
Abstract Background The abortion law in Cameroon is highly restrictive. The law permits induced abortions only when the woman's life is at risk, to preserve her physical and mental health, and on grounds of rape or incest. Unsafe abortions remain rampant with however rare reported cases of persecution, even when these abortions are proven to have been carried out illegally. Discussion Available public health interventions are cheap and feasible (Misoprostol and Manual Vacuum Aspiration in post abortion care, modern contraception, post-abortion counseling), and must be implemented to reduce unacceptably high maternal mortality rates in the country which still stand at as high as 596/100.000. Changes in the legal status of abortions might take a long time to come by. Albeit, advocacy efforts must be reinforced to render the law more liberal to permit women to seek safe abortion services. The frequency of abortions, generally clandestine, in this restrictive legal atmosphere has adverse economic, health and social justice implications. Conclusion We argue that a non-optimal or restrictive legal atmosphere is not an acceptable excuse to justify these high maternal deaths resulting from unsafe abortions, especially in Cameroon where unsafe abortions remain rampant. Implementing currently available, cheap and effective evidence based practice guidelines are possible in the country. Expansion and use of Manual Vacuum Aspiration kits in health care facilities, post-abortion misoprostol and carefully considering the content of post abortion counseling packages deserve keen attention. More large scale qualitative and quantitative studies nationwide to identify and act on context specific barriers to contraception use and abortion related stigma are urgently needed.